2002
DOI: 10.1111/1465-5922.00325
|View full text |Cite
|
Sign up to set email alerts
|

To speak in tongues: language, diversity and psychoanalysis

Abstract: After reviewing the different psychoanalytical approaches to language of authors such as Freud, Lacan, Kristeva, Jung and Nicolas Abraham, the author examines the problem of 'analytical listening', of the attitude that every analyst must assume towards the words of the analysand, words that must be heard not just in terms of their content but above all in terms of their sound. We live in a culture in which visual images predominate over acoustic images and all too often this cultural trend is repeated in analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…In the first scenario, Western therapists might gain knowledge and will be able to ask their Japanese clients if those stereotypes apply to that client's case. Traditional Japanese values and characteristics of communication styles are well documented (Connolly, 2002; Marsella, 1993; Marsella, Johnson, Johnson, & Brennan, 1998; Movahedi, 1996; Rothbaum et al, 2002). Therapists can therefore inquire about the meaning of that stereotype to the client and how the client is reacting to the therapist who presented that specific stereotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first scenario, Western therapists might gain knowledge and will be able to ask their Japanese clients if those stereotypes apply to that client's case. Traditional Japanese values and characteristics of communication styles are well documented (Connolly, 2002; Marsella, 1993; Marsella, Johnson, Johnson, & Brennan, 1998; Movahedi, 1996; Rothbaum et al, 2002). Therapists can therefore inquire about the meaning of that stereotype to the client and how the client is reacting to the therapist who presented that specific stereotype.…”
Section: Discussionmentioning
confidence: 99%
“…Simple miscommunication can be a source of confusion when more than one language is used. In addition, the most subtle parts of psychodynamic psychotherapy, such as client fantasies and early childhood experiences, are embodied in the language that was used at the time of those experiences (Connolly, 2002; Movahedi, 1996). Representing those experiences in a different language can be difficult, as can free association (a psychoanalytic concept also utilized in psychodynamic therapies to extract implicit memories by having the client verbalize to the therapist whatever comes to mind).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that having two languages at one's disposal can facilitate understanding of the client's experiences and foster communication. Connolly () found that bilingualism enabled her to make multiple links and associations in her work, which facilitated a deeper understanding of transference–countertransference and conflictual material. This process facilitated the acceptance of words as a source of sounds and rhythms rather than meaning, thus encouraging her to withhold from making interpretations and allowing her client to regress back to his/her preverbal state.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Thus, the words must be evaluated, listening beyond the content, analyzing the sound and the meaning of what was said 22 . For instance, the Lacanian psychoanalytic theory allows linking the communicative behavior and offers a set of symbolic coordinate 23 which may be escaping from the unconscious.…”
Section: Protocol Of Classification Of Studiesmentioning
confidence: 99%